More on the Neanderthal problem: the Vindija case - Karavanić, Ivor; Smith, Fred H. (2000)
Our interpretation of the association of Mousterian lithics and Upper Paleolithic bone and stone tools with Neandertal skeletal remains in level G1 of Vindija Cave, Croatia, has been strongly criticized by Zilhao and d'Errico in Current Anthropology (1999, 40:355-64). Essentially, they argue that the presence of these items in the same level is unequivocally the result of artificial mixing of remains from different strata of origin through the action of cryoturbation, bioturbation or both. However, while we recognize mixture as a possible explanation, we assert that Zilhao and d'Errico simplify the problem of the Middle/Upper Paleolithic interface at Vindija far too much. We also note some problems with their subjective assessment of edge damage on Vindija G1 lithics, an issue critical to our interpretation of the nature of G1 assemblage. Finally, we note that the recent AMS radiocarbon dating of Vindija G1 Neandertals adds additional support to the possibilility of cultural and biological integration of Neandertals and early modern humans by providing a temporal window of overlap between them in central Europe.
Projekt MZOS
ENG